MODEL PEMBERDAYAAN KELOMPOK WANITA TANI TERNAK DALAM BUDIDAYA AYAM BURAS DI KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Sutrisno Hadi Purnomo; Endang Tri Rahayu; Ina Nur Tanti (Universitas Sebelas Maret (UNS), 2016)
This research aim to investigate the profile of women farmers of livestock, supporting factors, inhibiting factors, the needs, and determine the model of empowerment through businesses that are appropriate for Group of Women Farmer Livestock (GWFL) in the cultivation of native chicken in the Banyudono Sub-district, Boyolali Regency. This research was conducted in Banyudono Sub-district, Boyolali Regency on 12 january until 5 march 2015. The method used in this research is the survey method. Intentionally, three villages namely Trayu, Tanjungsari and Bendan were chosen as the research location with the consideration that in these locations have GWFL are still actively contribute to the cultivation of native chicken. Samples were determined by census study to 67 people. The data collection was conducted through observation, interviews and Focus Group Discussion (FGD) with members of GWFL, Extension officer’s Boyolali Livestock Service, business partners and associated educational institutions. The data were analyzed by descriptive and analytical needs. The most important of needs factor for women livestock farmer in the cultivation of improved native chicken is the level of formal education, the availability and the conveniences access to educational facilities. The empowerment model of women farmers in Banyudono Sub-distric are providing non-formal education facilities, training and mentoring groups, and build working relationships with partners. The conclusion that can be drawn from this study that the empowerment model applied is the procurement of coaching and developing a native chicken farming as well as cooperation with supporting agencies.